Factors Associated with Acute Kidney Injury Occurrence and Prognosis in Rhabdomyolysis at the Emergency Department - Jun Seok Seo; Inhwan Yeo; Changho Kim; Daeun Kim; Jeong-Hoon Lim; Kyoungtae Park; Jiwoo Jeong; Hojin Kwon; Yuna Cho; Sungyeon Park (Medicina, 2024)
Background and Objectives: This study aimed to analyze patients with rhabdomyolysis who presented to emergency departments and identify their distribution of related disease and prognostic factors. Materials and Methods: A retrospective cohort study was conducted on patients with rhabdomyolysis who presented to emergency departments over a 10-year period. Patient data, including patients’ demographic variables (sex and age), mode of arrival, final diagnosis, statin use, rhabdomyolysis trigger factors, and levels of serum creatine phosphokinase (CPK), myoglobin, creatinine, sodium, potassium, phosphate, calcium, and lactate, were analyzed. Univariate and multivariate logistic regression analyses were conducted to identify the predictive factors of acute kidney injury (AKI). Results: Among the patients, 268 (65.6%) were found to have trigger factors without underlying diseases. Furthermore, 115 (28.2%) patients developed AKI. This comprehensive study sheds light on the diverse factors influencing the occurrence of AKI in rhabdomyolysis and provides insights into AKI predictive markers. Furthermore, we analyzed the cases by dividing them into six groups: occurrence of AKI, occurrence of infection, and simple or complex rhabdomyolysis. CPK time course was found to be important in clinical prognosis, such as AKI occurrence, dialysis or not, and mortality. Conclusions: Age, statin use, elevated creatinine and lactate levels, and initial serum CPK level emerged as significant predictors of AKI. CPK time course was also found to be an important factor in predicting the clinical outcomes of patients with rhabdomyolysis.